The Effectiveness of Facebook Social Media-Based Learning in Improving Student Learning Outcomes at MTs Islamiyah Bumi Agung - Muhammad Faisal Haqi (Edumaspul: Jurnal Pendidikan, 2024)
The selection of media to be used in the learning process is important. Facebook is one of the social media platforms that can be used to deliver subject matter during learning. This study aims to determine the effectiveness of using Facebook social media during learning to improve student learning outcomes at MTs Islamiyah Bumi Agung. This research was conducted at MTs Islamiyah Bumi Agung using two classes, namely class VII 1 as the experimental class and class VII 2 as the control class. This type of research is a type of quantitative research with the help of experimental methods using a true experimental design. The data collection technique in this study used a test instrument whose results were obtained from students of MTs Islamiyah Bumi Agung. The results of the study based on the results of statistical analysis using the t-test obtained a significance value (sig. 2-tailed) of 0.13 which is smaller than 0.05. So based on the t-test decision it can be concluded that if the significance value is smaller than 0.05 then H0 is rejected and Ha is accepted. This shows that there is a significant difference in student learning outcomes in Jurisprudence subjects between students who are taught using Facebook social media and not taught using Facebook social media.